Letter to Rodney Murphy from Jane Tolmach January, 2000 - Jane Tolmach:::::: (2000)
A letter to Rodney Murphy from Jane Tolmach requesting the agenda and notice of meetings of the County of Ventura Aviation Advisory Commission, the Oxnard Airport Authority, and the Oxnard Airport Mission Statement Committee.